(untitled) (Bangladesh Journal of Child Health, 2022)
Background: Seizure is one of the most common CNS complications among patients receiving chemotherapy for acute lymphoblastic leukemia (ALL). Seizures are seen in 8-13% of patients with ALL. Most seizure occurs during the induction and consolidation phases of treatment. However, not much is known about the risk factors of these seizure. Materials & Method: This prospective observational study was conducted in the department of Pediatric Hematology and Oncology, BSMMU. One hundred and five newly diagnosed admitted children with ALL aged >1 year to <18 years, from May 2017 to March 2018 for induction remission chemotherapy and who fulfilled the criteria of case definition were enrolled into this study. Results: This study showed that seizure frequency was14.3% in children with ALL getting induction remission chemotherapy. Female patients developed seizures more than males which was statistically significant by univariate analysis (p = 0.029) but was not found to be a risk factor by multivariate analysis (p = 0.059). All the seizures developed in B-lineage ALL but there was no statistically significant association between lineage of ALL with development of seizures. Conclusions: In this study slightly higher frequency of seizure in ALL patients on induction remission chemotherapy was found than previous studies (14.3% vs. 13%). Females developed seizures more than males. BANGLADESH J CHILD HEALTH 2021; VOL 45 (2) : 94-98